STRATEGY OF AL-HIDAYAH LIBRARY IN DEVELOPING INFORMATION LITERACY AMONG THE COMMUNITY OF NATAMBANG RONCITAN VILLAGE SOUTH TAPANULI - Hasibuan, Isro Hayati; Sayekti, Retno (Pena Cendekia Insani, 2025)
This study aims to analyze the strategy of the Al-Hidayah Library in developing information literacy among the people of Natambang Roncitan Village, South Tapanuli Regency. Information literacy is a crucial competency in the digital era, especially in supporting the development of inclusive and empowered rural communities. The research method used is descriptive qualitative with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study identified three main programs run by the library, namely poetry writing classes, basic computer training, and storytelling activities. The three programs not only improve the information literacy skills of the community, but also strengthen the role of the library as a center for community learning based on social inclusion. The success of the program implementation is supported by institutional support from the village government, active community participation, and librarian competence in utilizing information technology. The findings of this study indicate that the village library model based on participation and cross-party collaboration is effective in improving literacy and community empowerment. This study provides a conceptual contribution to the development of a community literacy model, as well as practical recommendations for sustainable village library management.